The Influence of Internet-Based Organizational Communication Through Organizational Commitment on Cross-Generation Employee Performance - Fachrurrazi, Muhammad (GoAcademica Research & Publishing, 2025)
The low employee performance and organizational commitment at PT Sari Ater Hot Springs Ciater. This issue is also marked by the suboptimal levels of employee performance, organizational commitment, and the lack of effectiveness in the application of Internet-Based Organizational Communication. Therefore, this study aims to determine how Internet-based organizational communication exhibits a substantial influence on employees' aptitude, with organizational commitment serving as an intermediary entity. The observational unit in this research encompasses 303 individuals employed at PT Sari Ater Hot Springs Ciater. The sample acquisition technique was executed through a purposive sampling scheme synergized with a non-probability sampling approach to ensure the inclusion of subjects aligning with the predetermined parameters. Furthermore, the conducted hypothesis testing affirms that internet-based organizational communication exerts a positive and significant influence on employee performance, with organizational commitment functioning as an intervening variable.